A117 PROPOFOL SEDATION DOES NOT IMPROVE MEASURES OF COLONOSCOPY QUALITY – FINDINGS FROM THE SOUTHWEST ONTARIO COLONOSCOPY COHORT. (4th March 2021) - Sey, M; Yan, B; Hindi, Z; Brahmania, M; Gregor, J C; Jairath, V; Wilson, A; Khanna, N; McDonald, C; cocco, S; Chakraborti, D; French, K; et al.
Abstract: Background: The use of propofol during colonoscopy has gained increased popularity due to deeper anesthesia compared to conscious sedation. Prior studies examining the use of propofol sedation during colonoscopy have primarily focused on anesthesia outcomes. Whether propofol sedation is associated with improvements in colonoscopy outcomes is uncertain. Aims: The primary outcome was adenoma detection rate (ADR). Secondary outcomes were the detection of any adenoma (conventional adenoma, sessile serrated polyp, and traditional serrated adenoma), sessile serrated polyp detection rate, polyp detection rate, cecal intubation rate, and perforation rate. Methods: The Southwest Ontario Colonoscopy cohort consists of all patients who underwent colonoscopy between April 2017 and Oct 2018 at 21 hospitals serving a large geographic area in Southwest Ontario. Procedures performed in patients less than 18 years of age or by endoscopist who perform <50 colonoscopies/year were excluded. Data were collected through a mandatory quality assurance form that was completed by the endoscopist after each procedure. Pathology reports were manually reviewed. Results: A total of 46, 634 colonoscopies were performed by 75 physicians (37.5% by gastroenterologists, 60% by general surgeons, 2.5% others) of which 16, 408 (35.2%) received propofol and 30, 226 (64.8%) received conscious sedation (e.g. combination of a benzodiazepine and a narcotic). Patients who received propofol were likely to have a screening indication (49.2% vs 45.5%, p<0.0001), not have a trainee endoscopist present and be performed at a non-academic centre (32.2% vs 44.6%, p<0.0001). Compared to conscious sedation, use of propofol was associated with a lower ADR (24.6% vs. 27.0%, p<0.0001) and detection of any adenoma (27.7% vs. 29.8%, p<0.0001); no difference was observed in the detection ofsessile serrated polyps (5.0% vs. 4.7%, p=0.26), polyp detection rate (41.2% vs 41.2%, p=0.978), cecal intubation rate (97.1% vs. 96.8%, p=0.15) or perforation rate (0.04% vs. 0.06%, p=0.45). On multi-variable analysis, the use of propofol was not significantly associated with any improvement in ADR (RR=0.90, 95% CI 0.74–1.10, p=0.30), detection of any adenoma (RR=0.93, 95% CI 0.75–1.14, p=0.47), sessile serrated polyp detection rate (RR=1.20, 95%CI 0.90–1.60, p=0.22), polyp detection rate (RR=1.00, 95% CI 0.90–1.11, p=0.99), or cecal intubation rate (RR=1.00, 95%CI 0.80–1.26, p=0.99). Conclusions: The use of propofol sedation does not improve colonoscopy quality metrics. Funding Agencies: None